Premenstrual Syndrome (PMS): Premenstrual Dysphoric Disorder (PMDD) - Dr. M. Asarnisa Begum (Tamil Psychiatry Journal, 2025)
In recent times, the importance of mental health among women has been increasing. Premenstrual syndrome is considered to be one of the most common and under-reported disorders in women’s lives. It causes great distress to women and reduces their quality of life, causing great distress to their emotions, and having a major impact on their performance and lifestyle. Although the symptoms of this disorder have been known since ancient times, the diagnostic criteria for this disorder have only been defined in recent times. Therefore, the definition of this disease has changed from the names of emotional disorders occurring before menstruation, premenstrual depression to premenstrual syndrome. This article explains what the premenstrual syndrome is, and the causes and symptoms of premenstrual syndrome. It also discusses the importance of dietary factors and their impact on PMS. Also, the various treatment modalities of PMS are discussed here.